How Funding Sources Affect Academic Experiences and Involvement: Gulf Arab International Students in the US Across the Disciplines (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
Graduate students from Arab Gulf countries earning degrees abroad are often funded by their governments, employers, or private institutions in their home countries, often making this funding sources different from their peers.  This qualitative case study of female international students from Arab Gulf countries in the US explores participants’ academic experiences in their graduate programs and focuses on how it was affected by their funding sources.  Data was collected with participants during spring and summer semester in 2018 at a land-grant university in the Midwest US. Findings show that the interactions that participants had based on their funding (or lack thereof) affected their overall experience and involvement with campus and the extent to which they had access to campus involvement.  The research finds that having an assistantship or not has some positive effects for some, has some negative effects for others, is a double-edged sword for some and quite unimportant to others. The degree to which participants’ funding affected their experience was affected by how much experience through assistantships was common in their programs, options for gaining experience in their fields and integration on campus outside of assistantships, departmental contexts, and their long-term goals. Additionally, the role of discrimination in the campus involvement of students from marginalized identities is discussed. Recommendations are made for considering funding sources when supporting students in order to promote their involvement in their departments and with the wider campus community while considering potential discrimination that increased involvement can have.